Peran Kepemimpinan Kolaboratif dalam Mewujudkan Visi dan Misi di Sekolah Menengah - Isep Budiman; Eli Sunarsah; Ika Sriyanti; Agus Mulyanto (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the role of collaborative leadership in realizing the vision and mission of high schools. Education as the main pillar of human resource development places the vision and mission of the school as a strategic guide in all educational activities. Collaborative leadership is understood as an approach that emphasizes cooperation between leaders and all team members to achieve common goals through active involvement in decision-making. This study uses a qualitative method with a case study approach at SMA Negeri 1 Pangkalan. The subjects of the study include principals, teachers, students, and parents. Data collection techniques are carried out through interviews, observations, and documentation. The results show that the application of collaborative leadership creates an environment that supports open communication and effective cooperation. Schools with collaborative leadership recorded up to 90% of vision and mission achievement, much higher than schools that did not implement this approach, which was 60%. The supporting factors are inclusive school culture, effective communication, and commitment from all stakeholders. The inhibiting factor is the lack of collaborative leadership training for principals and teachers.